2021
DOI: 10.3389/fmed.2021.741108
|View full text |Cite
|
Sign up to set email alerts
|

Levosimendan to Facilitate Weaning From Cardiorespiratory Support in Critically Ill Patients: A Meta-Analysis

Abstract: Background: Cardiopulmonary support, as extracorporeal membrane oxygenation (ECMO) or mechanical ventilation (MV), is crucial for ICU patients. However, some of these patients are difficult to wean. Therefore, we aimed to assess the efficacy and safety of levosimendan in facilitating weaning from cardiorespiratory support in this patient population.Methods: We searched for potentially relevant articles in PubMed, Embase, China National Knowledge Infrastructure, Wanfang, and the Cochrane database from inception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 35 publications
(112 reference statements)
1
16
0
1
Order By: Relevance
“…Further insights into this matter are provided by the meta-analysis of Luo et al [ 48 ] which draws on data from 2274 patients in 18 studies (RCTs or observational studies published in either Chinese or English). Pooled analysis from all 18 studies indicated that levosimendan improved MV/ECMO weaning ( n = 2274; OR 2.32; 95% CnI 1.60–3.36; p < 0.00001 vs control), albeit with high heterogeneity ( I 2 = 68%) and a general rating of evidence quality as low to moderate.…”
Section: Weaning From Va-ecmomentioning
confidence: 99%
“…Further insights into this matter are provided by the meta-analysis of Luo et al [ 48 ] which draws on data from 2274 patients in 18 studies (RCTs or observational studies published in either Chinese or English). Pooled analysis from all 18 studies indicated that levosimendan improved MV/ECMO weaning ( n = 2274; OR 2.32; 95% CnI 1.60–3.36; p < 0.00001 vs control), albeit with high heterogeneity ( I 2 = 68%) and a general rating of evidence quality as low to moderate.…”
Section: Weaning From Va-ecmomentioning
confidence: 99%
“…According to previous studies, levosimendan administration significantly increased successful weaning rates in patients with cardiopulmonary support, especially in those with combined poor LV performance (23)(24)(25)(26). Regarding the issue of VA-ECMO for patients with CS, the enrolled studies were nonrandomized studies with a limited number of patients (25).…”
Section: Levosimendan Administration For Weaning Venoarterial Extraco...mentioning
confidence: 99%
“…The use of levosimendan may provide a potential benefit in terms of VA-ECMO weaning success, reduce the duration of mechanical support, and minimize severe complications ( 23 , 24 ). Two studies concluded that levosimendan use in CS might reduce all-cause mortality and facilitate successful weaning from VA-ECMO ( 25 , 26 ). However, two recent studies showed that levosimendan did not improve the rate of successful VA-ECMO weaning in patients with refractory CS ( 27 , 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Venous-arterial extracorporeal membrane oxygenation (V-A ECMO) is an important circulatory support to rescue patients with refractory cardiogenic shock ( 1 , 2 ). However, the use of V-A ECMO can also lead to various complications ( 3 , 4 ), such as infection, hemorrhage, lung injury and skeletal muscle atrophy ( 5 ). Besides, prolonged V-A ECMO support was also associated with higher mortality ( 6 ), therefore, early weaning should be considered to maximize its benefits.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, nearly one third of 10.3389/fmed.2022.989197 deceased patients had once been weaned from ECMO (7). Of note, one of the major contributors for the death after weaning was heart failure (5).…”
Section: Introductionmentioning
confidence: 99%